2018
DOI: 10.1002/ijgo.12527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical, endocrine, and metabolic biomarkers for the early diagnosis of polycystic ovary syndrome among non‐obese Saudi women

Abstract: Various parameters could potentially be used as biomarkers to assess risk of PCOS, even among symptom-free non-obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…They uniformly showed higher insulin resistance, lower SHBG plasma levels, and greater evidence of hyperandrogenism in obese PCOS women compared to their normal weight counterparts [5,8,28]. The results of some the other studies demonstrated that insulin resistance was present in both obese and non-obese women with PCOS [29][30][31]. In this study, although obese PCOS individuals had lower SHBG levels, we did not find a significant difference in insulin resistance and testosterone level between obese and non-obese PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…They uniformly showed higher insulin resistance, lower SHBG plasma levels, and greater evidence of hyperandrogenism in obese PCOS women compared to their normal weight counterparts [5,8,28]. The results of some the other studies demonstrated that insulin resistance was present in both obese and non-obese women with PCOS [29][30][31]. In this study, although obese PCOS individuals had lower SHBG levels, we did not find a significant difference in insulin resistance and testosterone level between obese and non-obese PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased kisspeptin has been reported in several populations of PCOS patients (Albalawi et al 2018, Katulski et al 2018, Umayal et al 2019. Of note, not all populations of women with PCOS exhibit changes in kisspeptin levels (Daghestani 2018, Katulski et al 2018, inferring alterations in the KNDy system may be related to differences in PCOS phenotype or severity. Recent clinical studies also provide support for modulation of the KNDy system as a potential new target for the development of treatment for PCOS.…”
Section: Current Implications and Future Directions From Basic Researmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a reproductive endocrine metabolic disorder characterized by insulin resistance accompanied by persistent ovulation disorder and hyperandrogenemia (Elbohoty Ahmed et al, 2016). Western medicine believes that genetic factors, high luteinizing hormone, glycolipid metabolism disorder (Daghestani, 2018), hyperinsulinemia and insulin resistance (Giandalia), hyperandrogenemia (Li et al, 2018), low degree inflammatory reaction (Jamilian), obesity (Rezvan et al, 2018), abnormal ovarian function and hyperpuberty are the etiology and pathogenesis of PCOS (Leng and Wei, 2018, Zuo and Fu, 2018). PCOS belongs to the category of “late menstruation” and “amenorrhea” in traditional Chinese medicine (TCM).…”
Section: Introductionmentioning
confidence: 99%